INDONESIAN GOVERNMENT POLICY ON ROHINGYA REFUGEES - Deasy silvya Sari (Andalas Journal of International Studies (AJIS), 2018)
The wave of migration of Rohingya refugees has come unstoppably in the waters of Aceh since late 2015. The violence that engulfs the Rohingyas in Myanmar, such as homicide and arson, has forced some Rohingyas to flee. They are trying to survive by moving to areas they consider to be providing protection. With less decent boats, the Rohingyas migrated to the coast of Thailand, Malaysia, to Indonesia. The Armed Forces of the Republic of Indonesia have sought to close the refugee entry into the territory of the Unitary State of the Republic of Indonesia in order to safeguard the security of foreign infiltration. Nevertheless, the Indonesian army continues to assist the refugees by providing food and water supplies to the boat. However, the urge of local and international community finally made the Indonesian government open the territory of Indonesia for Rohingya refugees. Why is the Indonesian government willing to accept Rohingya refugees? What is Indonesian policy towards Rohingya refugees? This article will describe the reasons and steps of the Indonesian government to handle the wave of migration of Rohingya refugees by the end of 2015 as a form of Government of Indonesia's policy towards Rohingya refugees.